Overexpression of stromal interaction molecule 1 may promote epithelial-mesenchymal transition and indicate poor prognosis in gastric cancer - Wu, Guobin (Mol Med Rep, 2017)
The aim of the present study was to investigate the prognostic significance of stromal interaction molecule 1 (STIM1) expression in gastric cancer (GC) and examine the association between STIM1 and epithelial-mesenchymal transition (EMT). Immunohistochemical staining was performed to detect STIM1, E-cadherin, β-catenin and matrix metalloproteinase-9 (MMP-9) in 170 GC and 35 adjacent healthy gastric tissue samples. Positive staining of STIM1, E-cadherin, β-catenin and MMP-9 in GC tissues was significantly greater compared with adjacent healthy tissues (P<0.05). Clinicopathological analysis revealed that STIM1 expression was significantly associated with LNM (P<0.001) and tumor-node-metastasis stage (P=0.01). The overall survival rate was significantly reduced in STIM1-positive compared with STIM1-negative patients (P=0.043). Cox regression analysis indicated that STIM1 expression and LNM were independent prognostic factors for GC. Chi-square tests suggested that STIM1 expression in GC tissues was significantly associated with E-cadherin (P<0.001) and β-catenin (P<0.001), whereas no association was observed between STIM1 and MMP-9 expression (P>0.05). In conclusion, the results of the present study suggested that STIM1 may be a valuable prognostic marker in GC patients, and that STIM1 may increase GC motility and invasiveness by promoting epithelial-mesenchymal transition.